Co-authorship Network Analysis - Lengyel, Péter; Pancsira, János; Füzesi, István (International Journal of Engineering and Management Sciences, 2018)
The methodological basis of research on networks is given by graph theory. During the network analysis we work with a big data population and we are mainly analysing the relationships of the actors, which can be visualized with the graph network. The analysis of social network is becoming more and more popular in academic life as well. Most of the co-authorship networks are built around a number of prestigious people who manage their own network as a central player creating cliques.